Insecure attachment and the correlation with joining insurgent groups in Colombia (2009)
This study examined early childhood experiences in ex-insurgents from a Colombian paramilitary group (AUC) in order to determine whether their shared profile of difficult attachment is related with their joining the insurgency. One hundred fifty seven young adults were assessed using the Parental Bonding Instrument (PBI) (Parker, 1986). Results indicate that 99.4% of the sample (n=156) received insecure attachment classification and (n=1) received optimal parenting. The study highlights the importance of responsive and supportive care given during childhood.